Preparation method for regulating and controlling particle size of active metal nickel
By added to the preparation of the nickel -based catalyst, the restoration of combustion is added, and the oxidation reaction and local heat dissipation are used to uniformly decompose metal salt to prepare nickel particles with higher decentralized and smaller particle size, solving the nickel -based catalyst agent The problem of sintering and granular reunion at high temperatures significantly improves the performance and stability of the catalyst.
Patent Information
- Application Number
- CN202411555081.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-04
- Publication Date
- 2025-01-28
AI Technical Summary
The existing nickel-based catalysts are prone to sintering and particle agglomeration at high temperatures, resulting in a degradation of catalytic performance and poor stability, and lack of catalysts with good economical and excellent performance.
By adding two types of restored combustion, use the oxidation reaction and local insulation, uniformly decompose metal salt, and prepare nickel particles with higher decentralized and smaller particle size. The specific steps include the configuration CEO2 carrier. The impregnated solution is added with Ni (NO3) 2 · 6H2O as the front -drive body. The C2H5NO2 and NH4NO3 are used as a combustion. After drying and baking treatment, the catalyst is finally obtained.
A significant reduction of catalyst nickel -size size, improving the catalyst's carbon resistance and catalytic activity, enhancing the stability of the catalyst, especially showing better performance at high temperature.
Smart Images

Figure CN119368193A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of catalyst synthesis, and in particular to a preparation method for regulating the particle size of active metal nickel. Background Art
[0002] Coal and oil are still the most widely used fossil fuels. Their combustion process releases a large amount of carbon dioxide into the atmosphere, causing the concentration of carbon dioxide in the atmosphere to gradually increase, which in turn causes the temperature to rise. The hazards of climate change are becoming increasingly apparent, not only in extreme weather events, but also in a series of environmental problems such as glacier melting, ocean acidification and land desertification, which have adverse effects on human production and life. Experts predict that by 2100, global temperatures may rise by as much as 5.7°C, which will seriously threaten life on Earth. In fact, the natural system has undergone irreversible changes. Since 2010, carbon dioxide emissions have increased by an average of 1.4% per year. Capturing, storing and utilizing carbon dioxide is considered to be the most effective emission reduction strategy to curb this trend. Despite significant progress in carbon capture and storage, large amounts of stored carbon dioxide are still limited in practical application.
[0003] CH4 is the simplest alkane with a bond angle of 109.5° and is also the main component of natural gas. Traditionally, CH4 has two sources. First, CH4 comes from natural resources such as wetlands, grasslands, termites, lakes, coal seams, etc. Second, CH4 comes from human activities such as landfills, coal mining, oil and gas processing, agricultural activities, etc. Of the total sources of CH4, anthropogenic sources account for about 60%, and natural sources (mainly wetlands) account for about 40%. In 2021, the global average CH4 concentration reached 1908 parts per billion (ppb), which is more than 160% higher than the pre-industrial level (1750). This increase is mainly caused by human industrial activities. In addition, as the second largest greenhouse gas after CO2, CH4 has a greenhouse effect 27 times stronger than CO2, which has a serious impact on the environment. Therefore, in order to improve the chemical application value of CH4, converting CH4 into other valuable products is the current research focus of scientific researchers.
[0004] The reforming reaction of methane and carbon dioxide can generate synthesis gas (H2 and CO) while comprehensively utilizing greenhouse gases CH4 and CO2, and the synthesis gas can be used as the feed gas for Fischer-Tropsch synthesis or methanol synthesis. This reaction has positive significance in reducing carbon emissions and mitigating the greenhouse effect. However, there are certain technical difficulties in this reaction process, mainly manifested in the lack of catalysts with good economic efficiency and excellent performance. Due to its low cost and relatively high catalytic activity, supported nickel-based catalysts are one of the most attractive catalysts, and its activity is comparable to that of precious metal catalysts, and it is considered to be the most promising for application in industrial production. However, in practical applications, nickel-based catalysts face the problems of sintering of active components at high temperatures and deactivation caused by carbon accumulation on the surface during the reaction, so it is necessary to conduct in-depth research on its key structure and reaction mechanism. Studies have found that the particle size and dispersion of nickel particles of Ni-based catalysts have an important influence on the catalytic performance and stability. Highly dispersed Ni can effectively alleviate the problems of sintering and particle agglomeration of catalysts at high temperatures; small-particle active components help to improve the low-temperature activity and anti-carbon deposition performance of the catalyst. In addition, the dispersion is closely related to the nickel particle size. Generally, the smaller the active component grains, the more metal atoms are exposed on the carrier surface, and the higher the dispersion. Therefore, the design and preparation of efficient Ni-based catalysts can be carried out from the perspective of controlling the size of Ni nanoparticles, which is of great significance for improving their catalytic performance and stability, and provides ideas and inspiration for the development of new and efficient Ni-based catalysts for DRM reactions.
[0005] When the Ni particle size of the supported Ni-based catalyst is large, the metal dispersion is poor, which is not conducive to the stability of the catalyst; when the particle size is too small, the surface free energy is large, making the particles more inclined to aggregate. Therefore, there is an optimal particle size range for the Ni particle size, within which the catalyst has the best sintering inhibition effect. On the one hand, reducing the Ni particle size can improve the dispersion, hinder the aggregation and growth of metal particles, and thus improve the catalyst's anti-sintering ability. Some scholars have prepared Ni / MgAl2O4 and Ni / Al2O3 catalysts with a Ni loading of 5%. The Ni particle sizes are 10.4 nm and 26.5 nm, respectively, and the dispersions are 16% and 3%, respectively. They were used for DRM reaction at 750°C. After 10 hours, it was found that the Ni particle size of the Ni / MgAl2O4 catalyst with a smaller initial particle size only increased to 11.8 nm, while the Ni particles of the Ni / Al2O3 catalyst increased to 90.0 nm, and obvious sintering occurred. On the other hand, when the particle size is too small, the surface energy is large, and the particles are more inclined to aggregate. Studies have shown that when the metal particle size is less than 6.0 nm, the chemical potential of the transition metal nanoparticles loaded on the oxide carrier increases significantly as the particle size decreases, generating a greater sintering driving force; when the metal particle size is 6.0 nm, the sintering rate decreases significantly because the thermodynamic driving force decreases to near zero. Therefore, under the premise of no other measures to inhibit sintering, metal particles with a particle size of about 6.0 nm have a better sintering inhibition effect. Summary of the invention
[0006] The present invention overcomes the shortcomings of the prior art and provides a preparation method for regulating the particle size of active metal nickel. The present invention adds two reducing combustion agents, and the metal salt and the combustion agent react under thermal conditions to form corresponding metal oxides. The decomposition of the metal salt depends on high temperature and the occurrence of redox reaction. The oxidation reaction occurs rapidly, and under the simultaneous action of local heat release and ambient temperature, the combustion and decomposition of the metal salt are more uniform, so that metal particles with higher dispersibility and smaller particle size can be obtained.
[0007] In order to solve the above technical problems, the technical solution adopted by the present invention is: a preparation method for regulating the particle size of active metal nickel, comprising the following steps: (1) Configure CeO2 carrier; (2) Using Ni(NO3)2·6H2O as a precursor, C2H5NO2 and NH4NO3 as combustion agents, adding solvent to dissolve and prepare an impregnation solution; (3) adding the impregnation solution to the carrier obtained in step (1) and fully impregnating the carrier to obtain sample A; (4) Dry sample A at room temperature for 12 h, and then place it in a preheated drying oven and dry it for 12 h to obtain sample B; (5) Sample B is placed in a muffle furnace for calcination, and then tableted, ground, and sieved to obtain a catalyst.
[0008] As a further limitation of the technical solution of the present invention, the CeO2 carrier in step (1) is prepared by calcining the precursor Ce(NO3)2·6H2O at a calcination temperature of 450°C for 3h.
[0009] As a further limitation of the technical solution of the present invention, in step (2), the molar ratio of C2H5NO2, NH4NO3 and Ni(NO3)2 is 1:1:2.
[0010] As a further limitation of the technical solution of the present invention, in step (2), the solvent is a mixed solution of water and ethanol, and each 25 mL of the mixed solution contains 10 mL of water.
[0011] As a further limitation of the technical solution of the present invention, step (3) is performed at room temperature for 1 hour, during which stirring is performed every 10 minutes to ensure sufficient impregnation, and the loading amount of the active component Ni is 5 wt%.
[0012] As a further limitation of the technical solution of the present invention, the temperature of the preheating drying oven in step (4) is 110°C.
[0013] As a further limitation of the technical solution of the present invention, in step (5), the heating rate of the muffle furnace in static air is 5°C / min. -1 The calcination temperature is 400--800℃ and the calcination time is 3h.
[0014] As a further limitation of the technical solution of the present invention, the catalyst with a mesh size of 40-60 is obtained after sieving in step (5).
[0015] Compared with the prior art, the present invention has the following beneficial effects: The present invention adds two reducing combustion agents in a certain proportion, which significantly reduces the particle size of the catalyst nickel and greatly improves the catalyst performance compared with the traditional impregnation method. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 The present invention is a simplified process diagram of the method for preparing the active metal nickel particle size control.
[0017] Figure 2 This is the X-ray diffraction pattern (XRD) of the fresh catalyst sample prepared by the method of the present invention.
[0018] Figure 3 X-ray diffraction (XRD) pattern of fresh catalyst sample prepared by traditional impregnation method.
[0019] Figure 4The transmission electron microscope (TEM) spectrum and particle size distribution histogram of the catalyst sample prepared by the traditional impregnation method at a calcination temperature of 400°C.
[0020] Figure 5 The transmission electron microscope (TEM) spectrum and particle size distribution histogram of the catalyst sample prepared by the traditional impregnation method at a calcination temperature of 600°C.
[0021] Figure 6 The transmission electron microscope (TEM) image and particle size distribution histogram of the catalyst sample prepared by the traditional impregnation method at a calcination temperature of 800°C.
[0022] Figure 7 The transmission electron microscope (TEM) spectrum and particle size distribution histogram of the catalyst sample prepared at a calcination temperature of 400°C by the method of the present invention are shown.
[0023] Figure 8 The transmission electron microscope (TEM) spectrum and particle size distribution histogram of the catalyst sample prepared at a calcination temperature of 600°C by the method of the present invention are shown.
[0024] Fig. 9 The transmission electron microscope (TEM) spectrum and particle size distribution histogram of the catalyst sample prepared at a calcination temperature of 800°C by the method of the present invention are shown.
[0025] Fig.10 The particle size statistics of fresh catalyst samples prepared by different methods.
[0026] Fig.11 This is the initial activity test diagram of the catalyst; reaction conditions: CO2 / CH4 / N2 = 40 / 40 / 80mL / min, 500℃-700℃, 50℃ interval, 1atm.
[0027] Fig.12 This is a catalyst stability test diagram; reaction conditions: CO2 / CH4 / N2=40 / 40 / 80mL / min, 700℃, 1atm, 10h. DETAILED DESCRIPTION
[0028] The present invention is further described below in conjunction with specific embodiments. Example 1
[0029] like Figure 1As shown, the method of the present invention is used to prepare a 5 wt% Ni-based catalyst, comprising the following steps: preparing a CeO2 carrier by a nitrate direct calcination method; then using Ni(NO3)2·6H2O as an active component precursor, selecting C2H5NO2 and NH4NO3 as combustion agents, and using a water-ethanol mixed solution (containing 10 mL of water per 25 mL of solution) as a solvent due to the characteristics of the combustion agent not being easily soluble in ethanol, and configuring an impregnation solution with a material molar ratio of 1:1:2 between the combustion agent and the precursor; taking 0.95 g of the dried CeO2 carrier for impregnation, adding the impregnation solution according to the water absorption of the carrier, and impregnating for 1 hour at room temperature, stirring every 10 minutes during the period to ensure sufficient impregnation, and placing the obtained sample at room temperature for 12 hours after the impregnation, preheating the drying oven to 110°C, and then drying for 12 hours, then placing the sample in a muffle furnace, and drying at 5°C / min in static air. -1 The temperature was raised to different calcination temperatures (400°C, 600°C, 800°C) at a heating rate and maintained for 3 h. Finally, the catalyst samples were pressed, ground and sieved.
[0030] Figure 2 and Figure 3 As shown in the figure, the X-ray diffraction patterns of the sample prepared by the preparation method of the present invention and the sample prepared by the traditional impregnation method are analyzed by Jade and matched to determine that there are two phases, namely cubic NiO and cubic CeO2, and the PDF card numbers are PDF#97-000-9866 and PDF#04-003-5454 respectively. It can be determined from the relative intensity of the diffraction peaks that the content of cerium oxide as a carrier is relatively high, and the proportion of nickel oxide is relatively small. The strongest characteristic diffraction peak at 28.652 degrees is caused by the (111) crystal plane of cubic CeO2, the diffraction peak at 33.204 degrees corresponds to the (200) crystal plane, with a lattice spacing of 0.27nm, the strong diffraction peak at 47.665 degrees corresponds to the (220) crystal plane, with a lattice spacing of 0.19nm, the strong diffraction peak at 56.564 degrees corresponds to the (311) crystal plane, with a lattice spacing of 0.12nm, the weak diffraction peak at 59.323 degrees corresponds to the (222) crystal plane, the weak diffraction peak at 69.701 degrees corresponds to the (400) crystal plane, the diffraction peak at 77.028 degrees corresponds to the (331) crystal plane, with a lattice spacing of 0.12nm, and the weak diffraction peaks at 79.417 degrees and 88.832 degrees correspond to the (420) crystal plane and (422) crystal plane, respectively. In addition, there are two diffraction peaks corresponding to cubic NiO. Due to their small proportion, their relative intensity is low. The weak diffraction peak at 37.246 degrees is caused by the (111) crystal plane. The diffraction peak at 43.276 degrees with the largest relative intensity corresponds to the (200) crystal plane of NiO, and the lattice spacing is about 0.21nm.
[0031] like Figure 4-9As shown, the TEM images and particle size distribution histograms of the conventional impregnation method and the preparation method of the present invention at three calcination temperatures of A, B, and C (where A is 400°C, B is 600°C, and C is 800°C) are shown in sequence. It can be seen from the TEM images that the Ni particles of the catalyst prepared by the preparation method of the present invention are smaller, more evenly distributed, and more dispersed than those prepared by the conventional impregnation method. 150 data points were selected to make a particle size distribution histogram, which was compared with the particle size calculated by XRD characterization based on the Scherrer formula. The particle size change trend was the same, and the Ni particle size of the catalyst prepared by the present invention was significantly lower than that of the catalyst prepared by the conventional impregnation method.
[0032] like Fig.10 As shown, at a loading of 5%wt, the nickel particle size of the catalyst (Ni(C)CeO2) prepared by the preparation method of the present invention at three calcination temperatures of A, B, and C (where A is 400°C, B is 600°C, and C is 800°C) is reduced by 15.69%, 27.21%, and 17.24% respectively compared with the catalyst (Ni(I)CeO2) prepared by the conventional impregnation method. The nickel particle size of the catalyst prepared by the present invention is significantly lower than that prepared by the conventional impregnation method, and the range of the catalyst is smaller. Therefore, the addition of a suitable proportion of the combustion agent in the present invention can significantly reduce the size of the active metal particles, obtain smaller active metal particles, help improve the catalyst's ability to resist carbon deposition, and significantly improve the catalytic activity.
[0033] like Fig.11 As shown in the figure, from the results of the dry reforming reaction activity test of methane and carbon dioxide, it can be seen that the activity of the catalysts prepared by the two methods at different temperatures is significantly different, and the activity of each catalyst increases with increasing temperature. Overall, the performance of the catalyst prepared by the present invention is better than that of the catalyst prepared by the traditional impregnation method, especially at a higher temperature (700°C), the catalyst 5Ni(C) / CeO2-A achieved the highest methane (84%) and carbon dioxide (78%) conversion rate. The performance superiority of the catalyst prepared by the present invention is mainly reflected in higher activity and relatively small increase changes, showing better metal dispersion and metal-carrier interaction, thereby improving the overall catalytic performance.
[0034] like Fig.12As shown in the figure, the stability test was completed at 700 ° C for 10 hours to compare the deactivation characteristics of different catalysts during the reaction. As the reaction proceeded, the catalyst in the traditional impregnation system showed a more obvious deactivation trend. Especially for C, the conversion rate of CH4 had dropped to about 55% after 600 minutes, showing a weaker anti-deactivation ability. In contrast, although the conversion rate of B also decreased, it maintained a more stable activity and showed better anti-deactivation performance. In the system of the present invention, the catalyst of A showed the strongest stability, and its CH4 conversion rate remained at about 80% after 600 minutes, which was significantly better than other catalysts. In addition, although the conversion rate of B was lower than that of A, the downward trend was relatively slow, showing relatively stable catalytic performance. Although the initial conversion rate of C was low, the conversion rate was still maintained above 60% after 600 minutes of reaction.
[0035] From the overall trend, the catalyst in the system of the present invention has better anti-deactivation performance than the catalyst in the traditional impregnation method system, especially under long-term reaction conditions, the system of the present invention shows higher stability and is suitable for long-term catalytic reactions. Therefore, the present invention can significantly improve the anti-deactivation performance of the catalyst.
Claims
1. A method for preparing active nickel particles by adjusting their particle size, characterized in that: The following steps are involved: (1) Configure CeO2 carrier; (2) Using Ni(NO3)2·6H2O as a precursor, C2H5NO2 and NH4NO3 as combustion agents, adding solvent to dissolve and prepare an impregnation solution; (3) adding the impregnation solution to the carrier obtained in step (1) and fully impregnating the carrier to obtain sample A; (4) Dry sample A at room temperature for 12 h, and then place it in a preheated drying oven and dry it for 12 h to obtain sample B; (5) Sample B is placed in a muffle furnace for calcination, and then tableted, ground, and sieved to obtain a catalyst.
2. A method for preparing active nickel particles according to claim 1, characterized in that: The CeO2 carrier in step (1) is prepared by calcining the precursor Ce(NO3)2·6H2O at a calcination temperature of 450°C for 3 hours.
3. A method for preparing active nickel particles according to claim 1, characterized in that: In step (2), the molar ratio of C2H5NO2, NH4NO3 and Ni(NO3)2 is 1:1:
2.
4. A method for preparing active nickel particles according to claim 1, characterized in that: The solvent in step (2) is a mixed solution of water and ethanol, and each 25 mL of the mixed solution contains 10 mL of water.
5. The method for preparing active nickel particles according to claim 1, characterized in that: Step (3) was performed at room temperature for 1 hour, during which stirring was performed every 10 minutes to ensure sufficient impregnation. The loading amount of the active component Ni was 5 wt%.
6. A method for preparing active nickel particles according to claim 1, characterized in that: The temperature of the preheating drying oven in step (4) is 110°C.
7. A method for preparing active nickel particles according to claim 1, characterized in that: In step (5), the heating rate of the muffle furnace in static air is 5°C / min. -1 The calcination temperature is 400-800℃ and the calcination time is 3h.
8. The method for preparing active nickel particles according to claim 1, characterized in that: After sieving in step (5), a catalyst with a mesh size of 40-60 is obtained.